The many ways of being Muslim: the practice of immanent critique in Mohja Kahf’s The Girl in the Tangerine Scarf - Amrah Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
There is a stereotypical understanding of Islam as a religion that is inherently hostile to critique and changes, making it no longer relevant in modern age. To dispel this, Irfan Ahmad proposes the theory of immanent critique in the Islamic tradition where doctrines within the Islamic tradition itself are used to develop different interpretations of religious understanding. This article discusses how this theory is applied in the novel, The Girl in the Tangerine Scarf by Mohja Kahf (2006). It narrates the coming of age story of a young American Syrian Muslim woman, Khadra Shamy, who lives within a pious small Muslim community in Indiana, United States of America. As she lives under the watchful eyes of her parents and the community, she grapples with her understanding and acceptance of various Muslim communities around America who have different ways of practicing the religion. The article uses Ahmad’s theorization to discuss how the practice of critique allows the protagonist to free herself from being governed by specific individuals in her understanding of Islam. The concept allows the protagonist to actively engage with Islamic teachings in order to develop their personal position within the doctrines of the religion. Furthermore, the article also suggests that the practice of critique helps to develop an independent selfhood that is strongly committed to Islam while at the same time, tolerant of differences that may exist in the society that she is living in.